2017
DOI: 10.1016/j.fuproc.2017.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocarbon bio-oil production from pyrolysis bio-oil using non-sulfide Ni-Zn/Al2O3 catalyst

Abstract: Upgraded bio-oil can partly replace fossil fuels to reduce the environmental issues caused by the massive consumption of fossil fuels.Hydrodeoxygenation is a promising route for upgraded bio-oil production from pyrolysis bio-oil. Non-sulfide catalysts are effective in bio-oil hydrodeoxygenation due to low cost and high activity. Ni-Zn/Al 2 O 3 catalysts were first used to selectively produce hydrocarbon upgraded bio-oil through bio-oilhydrodeoxygenation.Upgrading pine sawdust bio-oil to upgraded hydrocarbon bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…As shown in Figure 7, the TG and DTG curves of both the used 3Ni/SAPO‐11 and as‐prepared 3Ni‐6Co/SAPO‐11 catalysts have two distinct regions of weight loss, that is, the weight loss below 200°C is attributed to desorption of water and organics adsorbed on the surface of the catalysts, and the another ranging from 200°C to 800°C is ascribed to the oxidation of coke deposited on the catalysts 38,39,41 . Notably, the weight loss of the used 3Ni‐6Co/SAPO‐11 catalysts is lower than that of the used 3Ni/SAPO‐11 catalysts, indicating that the addition of Co species improves the coking‐resistance of the catalysts for the HDO and isomerization of FAMEs, possibly resulted from the formation of the Ni‐Co alloy‐like phase 41 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 7, the TG and DTG curves of both the used 3Ni/SAPO‐11 and as‐prepared 3Ni‐6Co/SAPO‐11 catalysts have two distinct regions of weight loss, that is, the weight loss below 200°C is attributed to desorption of water and organics adsorbed on the surface of the catalysts, and the another ranging from 200°C to 800°C is ascribed to the oxidation of coke deposited on the catalysts 38,39,41 . Notably, the weight loss of the used 3Ni‐6Co/SAPO‐11 catalysts is lower than that of the used 3Ni/SAPO‐11 catalysts, indicating that the addition of Co species improves the coking‐resistance of the catalysts for the HDO and isomerization of FAMEs, possibly resulted from the formation of the Ni‐Co alloy‐like phase 41 …”
Section: Resultsmentioning
confidence: 99%
“…It confirms that addition of Cu into supported Nibased catalysts promotes the dispersion and reducibility of NiO, specifically forming the active Ni-Cu clusters after reduction. When oxophilic metals, such as Mo, 35,36 Fe, 37,38 and Zn, 39 are introduced into Ni catalysts, the activity and selectivity of the bimetallic catalysts for HDO are further enhanced because of the synergy effect between Ni for cleavage of H-H bonds and oxophilic metal for cleavage of C-O bonds. Likewise, metal Co also has a strong affinity for oxygen, which allows for easier activation and cleavage of C-O bonds.…”
Section: Introductionmentioning
confidence: 99%
“…In their study, the chemical compounds found in bio-oil from the pyrolysis of sludge palm oil consisted of hydrocarbons (76%), esters (8%), alcohols (13%), and ketones (3%). A very different result in terms of the hydrocarbons content of the bio-oil came from another study [39], where it was found that the hydrocarbon content of bio-oil produced by pyrolysis of pine sawdust was 16.94%. It was very likely that this significant difference in the hydrocarbon content of the two studies was due to the different raw materials used to produce bio-oil.…”
Section: Chemical Content Analysis Of Bio-oilmentioning
confidence: 94%
“…5 Biomass resources have been paid increasing attention because of their renewability and biodegradability. 6 In particular, the composition and energy utilization of biomass energy are very similar to those of fossil energy. Thus, it has the largest potential to substitute for conventional energy.…”
Section: Introductionmentioning
confidence: 99%